Etnomatemática nos manguezais: um estudo sobre o extrativismo de caranguejos no sul da bahia - Brasil - Dias Cardoso, Gracimar; de Freitas Madruga, Zulma Elizabete (Góndola, enseñanza y aprendizaje de las ciencias, 2026)
This article presents a theoretical essay, part of an ongoing dissertation in the Graduate Program in Science and Mathematics Education, at the State University of Santa Cruz, Ilhéus, Bahia, Brazil. The guiding question is: how can Ethnomathematics reveal the mathematical knowledge present in crab harvesting? To answer this question, the objective is to analyze the intersection between Ethnomathematics and crab harvesting practices in the cities of Ilhéus, Una and Canavieiras, in southern Bahia, Brazil. This is a qualitative research, in which documentary analysis was used. The aim was to identify actions that highlight the local knowledge present in the cultural practices of these communities, proposing its incorporation into the teaching of Mathematics, in a contextualized way and valuing cultural diversity. By integrating mathematical knowledge from crab harvesting into the school curriculum, the study contributes to a more inclusive and meaningful pedagogical approach for students, which breaks with the Eurocentric view of Mathematics and reveals cultural/local knowledge and practices. This essay encourages discussions on possibilities for planning educational experiences in the thematic units of numbers, algebra, quantities and measurements, and geometry, which connect theory and practice. Actions of this nature, with the development of pedagogical proposals of this nature in the classroom, are a perspective for continuing this investigation. The research points to an opportunity for Mathematics Education, expanding the understanding of the cultural specificities of the region, and above all the appreciation of local cultures. Furthermore, this study emphasizes the relevance of integrating this knowledge into the school curriculum, breaking with the Eurocentric perspective of Mathematics and encouraging a more contextualized and accessible approach for the student.